Peran Ahli Gizi Dalam Memberikan Pelayanan Gizi Berbasis Gen di Indonesia: Peran Ahli Gizi Dalam Memberikan Pelayanan Gizi Berbasis Gen di Indonesia - Alfiana, Rina; Aji, Arif Sabta; Samutri, Erni; Paratmanitya, Yhona; Hafizhah, Rafiqah Dwita; Zulfa, Ifana Fitria; Putri, Sintia Aurilia; Farhan, Alfina Ulfah; Surendran, Shelini (Universitas Airlangga, 2023)
Background: The rapid development of genetics science provides significant impacts on disease prevention and control. In Indonesia, the application of dietetics is not popular. Thus, the role of nutritionists in the application of nutritional genomics in dietetic work practices is highly needed. The role of nutritionists is important in providing information about how nutrition and genetics interact in influencing health and providing alternative early nutritional interventions. Objectives: Identify the role of nutritionists in providing gene-based nutrition services in Indonesia. Methods: This qualitative study used a phenomenological approach. This study was carried out in five provinces in Indonesia. Informant data were obtained from quantitative research. The determination of the informant used a purposive sampling technique involving six informants. Data were collected by conducting structured interviews online using Zoom Meeting. Data were analyzed using thematic analysis with NVIVO v.12 software. Results: Most nutritionists who have and have not implemented gene-based nutrition services know about gene-based nutrition services. However, some do not know the meaning of nutrigenetics and nutrigenomics. Besides, they know the role of nutritionists, namely as a counselor to provide counseling, provide advice regarding diet according to the patient's needs, and provide motivation to patients to follow a diet according to the patient's needs. Conclusions: In providing gene-based nutritional services, nutritionists play a role as counselors to provide counseling, provide advice regarding patient needs, and provide motivation to patients to adopt a diet according to patient needs.